2023
DOI: 10.3847/2041-8213/acf12c
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of the Self-organized Criticality Phenomenon in Precursors of Gamma-Ray Bursts

Xiu-Juan Li,
Yu-Peng Yang

Abstract: Precursors provide important clues to the nature of gamma-ray burst (GRB) central engines and can be used to contain GRB physical processes. In this Letter, we study the self-organized criticality in precursors of long GRBs in the third Swift/Burst Alert Telescope catalog. We investigate the differential and cumulative size distributions of 100 precursors, including peak flux, duration, rise time, decay time, and quiescent time with the Markov Chain Monte Carlo technique. It is found that all of the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…That is, the q values in q-Gaussian distributions are nearly invariant for different temporal interval scales, implying a scale-invariant structure in earthquakes (see also Wang et al 2015). Analogous scale-invariant characteristics have also been discovered in some astronomical phenomena, such as SGRs (Chang et al 2017;Wei et al 2021;Sang & Lin 2022), the repeating FRB 20121102 (Lin & Sang 2020;Wei et al 2021), GRB X-ray flares (Wei 2023) and precursors (Li & Yang 2023), and gamma-ray flares of the Sun and the blazar 3C 454.3 (Peng et al 2023). Given the temporal coincidences between the glitch/antiglitch and FRB-like bursts from the Galactic magnetar SGR J1935+2154 (Ge et al 2022;Younes et al 2023), here we examined their possible physical connection by comparing the scale-invariant similarities between repeating FRBs and glitching pulsars.…”
Section: Summary and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…That is, the q values in q-Gaussian distributions are nearly invariant for different temporal interval scales, implying a scale-invariant structure in earthquakes (see also Wang et al 2015). Analogous scale-invariant characteristics have also been discovered in some astronomical phenomena, such as SGRs (Chang et al 2017;Wei et al 2021;Sang & Lin 2022), the repeating FRB 20121102 (Lin & Sang 2020;Wei et al 2021), GRB X-ray flares (Wei 2023) and precursors (Li & Yang 2023), and gamma-ray flares of the Sun and the blazar 3C 454.3 (Peng et al 2023). Given the temporal coincidences between the glitch/antiglitch and FRB-like bursts from the Galactic magnetar SGR J1935+2154 (Ge et al 2022;Younes et al 2023), here we examined their possible physical connection by comparing the scale-invariant similarities between repeating FRBs and glitching pulsars.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…Furthermore, such a q-Gaussian behavior does not depend on the time interval adopted for the fluctuation, i.e., the q values in q-Gaussian distributions are approximately equal for different temporal interval scales, which implies that there is a scale-invariant structure in FRB 20121102 (Lin & Sang 2020;Wei et al 2021). Analogous scale-invariant characteristics have also been found in earthquakes (Caruso et al 2007;Wang et al 2015), soft gamma-ray repeaters (SGRs; Chang et al 2017;Wei et al 2021;Sang & Lin 2022), X-ray flares (Wei 2023) and precursors (Li & Yang 2023) of gamma-ray bursts (GRBs), and gamma-ray flares of the Sun and the blazar 3C 454.3 (Peng et al 2023). It is suggested that scale invariance is the most essential hallmark of a self-organized criticality (SOC) system (Caruso et al 2007;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 87%